The Moderating Effect Of Audit Quality On Audit Committee And Financial Reporting Quality In Malaysia - Hasan, Shahanif; Jatiningrum, Citrawati; Fauzi, Fauzi; Ali Abdul-Hamid, Mohamad (Opción, 2019)
This study investigates the exsistence of audit quality on the relationship between audit committee and financial reporting quality (FRQ) in Malaysia companies. Specifically, this study has examined several the mechanism of Corporate Govern- ance in Malaysia to the earnings management as proxied of FRQ. The study used 93 of listed trading companies on bursa Malaysia and the data analyzed with mul- tiple regression analytical technique. The results show that corporate governance mechanism (audit committee independence, audit committee financial expertise, audit committee size) not supported and insignificant result with FRQ. While, audit committee meeting has a significant result on FRQ. However, this study also re- veals that a decreased of FRQ would be a result of arisen discretionary accruals and poor of audit quality companies. Despite the absence of influenced the audit quality as moderating, but the finding show that Audit Quality increasing the relationship. These finding expected to help regulators better understand EM in Malaysian com- panies and this study may help them reconsider and review the accounting stand- ards across different sectors and to develop more effective techniques for quality financial reporting for Malaysian listed companies to enhance the credibility of financial reports.